A bounded-error approach to simultaneous state and actuator fault estimation for a class of nonlinear systems. (April 2017) - Buciakowski, Mariusz; Witczak, Marcin; Puig, Vicenç; Rotondo, Damiano; Nejjari, Fatiha; Korbicz, Józef
Abstract : Highlights: An approach for actuator fault estimation for nonlinear systems with simultaneous unknown input decoupling is proposed. Quadratic boundedness (QB) approach is used to overbound the estimation error. The LMI theory is applied for designing the UIO observer. Simulation results for a quadruple-tank system show the effectiveness of the proposed approach. Abstract: This paper proposes an approach for the joint state and fault estimation for a class of uncertain nonlinear systems with simultaneous unknown input and actuator faults. This is achieved by designing an unknown input observer combined with a set-membership estimation in the presence of disturbances and measurement noise. The observer is designed using quadratic boundedness approach that is used to overbound the estimation error. Sufficient conditions for the existence and stability of the proposed state and actuator fault estimator are expressed in the form of linear matrix inequalities (LMIs). Simulation results for a quadruple-tank system show the effectiveness of the proposed approach.